BEYOND THE VULTURE EYE: DECONSTRUCTING LANGUAGE, MADNESS, AND AUTHORITY IN POE’S PARAGON THROUGH CRITICAL DISCOURSE ANALYSIS - Ahmer Rauf; Faiqa Javed; Prof. Dr. Zia Ahmed (International Journal of Contemporary Issues in Social Sciences, 2024)
This study investigates the deconstruction of language in a short story. This research aims at examining the complex interplay between language, madness, and authority. This examination works on the short story The Tell-Tale Heart (1843) by Edgar Allan Poe. The focus of this analysis is to identify the linguistic elements contribute to the representation of authority, inviting readers or interpreters to reconsider the story’s traditional interpretations. The purpose of the present study is to encounter the effects caused by the use of well-structured narratives. Model of Critical Discourse Analysis (CDA) (Faircloug,1995) is applied for the analysis of the study. The data is collected by non-random sampling technique. The mixed method approach is applied to the study. This review leads to the perspective that how the vulture eye becomes a symbolic focal, how linguistic choices craft a chilling atmosphere. The findings highlight the understanding of the protagonist’s psychological descent, power dynamics and diversity, broader manipulation of discourse. The survey aims to deconstruct the symbols, semiotic analysis of the text of Poe’s short story. The future recommendations include psycholinguistic exploration, cultural studies with broader perspectives.